The design of an electronic voting machine with a GSM module - Mangwayana, Ignatio (Midlands State University, 2018)
The main objective of this project was to design a cost effective and efficient electronic voting system interfaced with a GSM module. There is need to replace the conventional voting system based on paper in Zimbabwe and many African countries by electronic voting machines which are cheaper, more secure and less cumbersome. Voting is when societies or a particular group of people come up with decisions based on choice and or preferences hence the need for a cheaper, more secure, reliable, transparent and less cumbersome system. A voting system of this nature will significantly reduce the draining of the much needed resources of the Zimbabwean economy and many other African countries. Costs linked to time, personnel, accommodation, food, stationery and transport are significantly reduced.